A review of the genus Changiola (Orthoptera: Grylloidea: Pteroplistinae) and description of the first species from Borneo - Tan, Ming Kai; Muhammad, Amira Aqilah; Robillard, Tony (Zootaxa, 2021)
The taxonomy of the little-known cricket genus Changiola from the subfamily Pteroplistinae is reviewed here. This genus consisted of three species, two from Malay Peninsula and one from Indochina. Here, we describe a new species from Borneo, the first from the island: Changiola sarawakensis n. sp. We also provide a key to the species, although it is likely that more species will be added to this genus with more sampling in the region.